The zeros of certain weakly holomorphic Drinfeld modular forms - Choi, SoYoung; Im, Bo-Hae (Manuscripta mathematica, 2014)
Duke and Jenkins (Pure Appl Math Q 4(4):1327–1340, 2008 ) constructed a canonical basis for the space of weakly holomorphic modular forms for SL 2 ( Z ) and investigated the zeros of the basis elements. In this paper we give an analogy in the Drinfeld setting of the result given by Duke and Jenkins (Pure Appl Math Q 4(4):1327–1340, 2008 ).